Study on character recognition algorithm for end face of bundled special steel bars - Fuxiang ZHANG (Hebei University of Science and Technology, 2021)
In order to realize the traceability of the whole process of special steel bar production information,the production environment and shape characteristics of special steel bar were analyzed.The marking scheme based on double mark points was adopted,and the machine vision technology was used to realize the character recognition of the end face of the bundled special steel bars.First,Hough transform was used to segment the end face image of the bundle of special steel bars into single ones.Secondly,an image enhancement algorithm based on wavelet transform was used to enhance the end face image of a single special steel bar.Then,the MSER algorithm and the edge detection algorithm were combined to complete the detection of the character area of a single special steel bar,and the character segmentation was completed based on the projection method.Finally,the end face character recognition of each special steel bar was completed by creating and training an SVM classifier,and the end face character recognition results of the bundle of special steel bars were output and saved.The results show that the new algorithm can meet the requirements of character identification in the production process of bundles,and the accuracy of character recognition can reach [BF]97.35%[BFQ].With combination of the Hough transform,the wavelet transform image enhancement algorithm,MSER algorithm,edge detection algorithm,projection method,and SVM classifier and other algorithms to character identification of special steel bar end face,the new algorithm provides reference for information acquisition,information transfer and information traceability of special steel bar production.[HQ][HQ]